The Effect Of Using Class Activities On Developing Numerical Sense Skills Among Basic Seventh Graders (A semi-Empirical Study In The City Of Lattakia) - نصور رغداء (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This study aimed to know the effect of using classroom activities on mathematics education to develop numerical sense choices among basic seventh-grade primary students. To achieve this goal, the researcher built the educational material based on class activities and presented it to a group of arbitrators and then tried it before the final application, The numerical sense test was applied to pupils after completing the teaching of the educational subject ,and the study sample reached 60 pupils from the seventh basic class in the city of lattakia divided into two experimental and control groups. The results of the study showed a difference between the mean scores of the experimental and control groups in the post application of the numerical sense test, and the superiority of the students of the experimental group may be attributed to the use of class activities in teaching unit numbers and operations on them, whereas, teaching in this way has contributed to developing numerical sense skills among the students of the experimental group better compared to the usual method .The study also showed a difference between the mean scores of the experimental group in the pre and post applications for the numerical sense test in favor of the post application, The researcher suggested relying on the classroom activities in teaching mathematics and all the academic stages due to its importance in increasing and developing numerical sense skills for students and thus achieving the goals of mathematics curricula.